A comparison of clinical and radiographic caries diagnosis on posterior teeth of children seen at a Nigerian Teaching Hospital. (2010)
caries is the most effective means of ensuring resolution of the condition and its sequelae. The aim of this study was to compare the effectiveness of clinical and radiographic (using bitewing radiograph) methods of caries diagnosis in children. The subjects were 172 children within the age range of 5-12 years attending the Paedodontic Clinic of the University College Hospital for the first time. They were clinically examined for the presence of dental caries using the WHO criteria. Left and right bitewing radiographs were taken following the clinical examination to detect dental caries. Clinical examination found additional 4 occlusal caries (incipient caries) that were not diagnosed radiographically and radiographic examination revealed additional 20 approximal surface caries that were not evident clinically in deciduous teeth. In permanent teeth, 3 additional occlusal caries were diagnosed clinically while only one additional approximal caries was diagnosed radiographically. These observations revealed the additional diagnostic value of bitewing radiograph in the diagnosis of approximal caries in children and the importance of clinical examinations in diagnosis of early occlusal caries (incipient caries) which are difficult to see on dental radiographs. In view of these findings, the use of bitewing radiographs combined with careful clinical examination will be of great advantage in early detection of caries in children